An examination of the flexion-relaxation phenomenon in the cervical spine in lumbo-pelvic sitting - Burnett, A.; O'Sullivan, Peter; Caneiro, J.; Krug, R.; Bochmann, F.; Helgestad, G. (Elsevier Science Ltd, 2009)
The flexion-relaxation phenomenon (FRP) is well documented at end-range lumbar spine flexion in both standing and sitting however, the FRP has been insufficiently investigated in cervico-thoracic musculature. The aim of this study was to determine whether the FRP occurs during forward flexion of the neck, in lumbo-pelvic sitting, amongst a pain-free population. Surface electromyography (EMG) was used to measure muscle activation in 20 (10 men, 10 women) asymptomatic subjects in selected cervico-thoracic muscles during four, 5-s phases (upright posture, forward flexion, full flexion and return to upright) while subjects were positioned in lumbo-pelvic sitting. Spinal kinematics were simultaneously measured using an electromagnetic motion tracking device. No FRP was observed in upper trapezius or thoracic erector spinae (T4). When using visual methods to determine the presence/absence of the FRP, five subjects were believed to show evidence of the FRP in the cervical erector spinae. However, when using various non-visual criteria to determine the existence of the FRP, substantial variations (0-13 subjects) were evident. We recommend that criteria based upon relatively large differences in muscle activation should be considered when defining the FRP. These findings are of significance for future investigations examining specific cervical pain disorders. © 2008 Elsevier Ltd. All rights reserved.